2022
DOI: 10.1371/journal.pone.0267773
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and challenges of parents caring for children with attention-deficit hyperactivity disorder: A qualitative study in Dar es salaam, Tanzania

Abstract: Background Attention-deficit hyperactivity disorder (ADHD) is the most common neurobehavioral childhood disorder. Children with ADHD are difficult to handle due to the symptoms causing great impairments such as inattention, hyperactivity compared to other childhood mental disorders. Having a child with ADHD is a stressful situation as it impacts the whole family. However, little is known about the experiences and challenges of parents caring for children with ADHD in low and middle-income countries such as Tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The situation aggravated financial constraints, ruined the family economy and caused further difficulties for participants to cater for the basic needs of their families, as had also been reported in previous studies 56 . Family financial challenges had been reportedly contributing to a delay in the initiation of cervical cancer treatment and interfering with the course of treatment 9,11,57 . As also reported previously, the government and stakeholders, such as charity organizations are key players in easing the accessibility and affordability of health insurance that covers treatment costs and granting financial aid to patients incapable of paying for their medical expenses 56 …”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The situation aggravated financial constraints, ruined the family economy and caused further difficulties for participants to cater for the basic needs of their families, as had also been reported in previous studies 56 . Family financial challenges had been reportedly contributing to a delay in the initiation of cervical cancer treatment and interfering with the course of treatment 9,11,57 . As also reported previously, the government and stakeholders, such as charity organizations are key players in easing the accessibility and affordability of health insurance that covers treatment costs and granting financial aid to patients incapable of paying for their medical expenses 56 …”
Section: Discussionmentioning
confidence: 83%
“…Challenges in sexual relationships were also revealed in a study by Solli et al among male caregivers of cervical cancer patients, and they reported that they received little information from health professionals concerning postcancer sexuality 15 . These sexual and reproductive concerns affect relationships, resulting in emotional stress, harsh treatment, and separation of families, which ultimately complicate cervical cancer treatment, as it has been reported in previous studies 9,58 . Vermeer et al revealed that many cervical cancer patients and their partners experienced sexual dysfunction overly due to psychosexual distress, and participants expressed the need for psychosexual support from the HCPs, but the medical attention was mainly on physical functioning 10 …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Caregivers faced challenges handling children with impaired functioning due to ADHD symptoms. These difficulties present a unique caregiving challenge distinct from other childhood mental illnesses (Ching'oma et al, 2022). Evidence-based parent training programs for preschoolers with ADHD, such as those modifying caring behaviors and improving symptoms and emotional, behavioral and social functioning (Feng et al, 2023), are crucial.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study showed that South African parents experienced difficulties such as negative emotions, economic problems, inadequate social support, stigma, and extra care giving responsibilities [ 18 ]. Tanzanian parents experienced difficulties in handling children whose level of functioning was impaired due to abnormal and disruptive behaviour such as not being able to follow parental instructions [ 19 ]. They are also faced with psychological problems due to caring demands exacerbated by a lack of support and stigma from the community, disruptions in family functioning and social interactions among family members.…”
Section: Introductionmentioning
confidence: 99%